1991
DOI: 10.1042/bj2750269
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal storage of subunit c of mitochondrial ATP synthase in Batten's disease (ceroid-lipofuscinosis)

Abstract: Immunochemical studies demonstrate that subunit c of mitochondrial ATP synthase is stored in the late-infantile, juvenile and adult forms of Batten's disease. It does not accumulate in the infantile form, or in other conditions involving lysosomal hypertrophy. These results suggest that the defective metabolism of subunit c is central to the pathogenesis of these three forms of Batten's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(83 citation statements)
references
References 17 publications
(12 reference statements)
7
76
0
Order By: Relevance
“…Additional proteins are variably associated with the isolated storage bodies, but these have not been well characterized. For example, Hall and colleagues analysed the protein compositions of storage bodies isolated from brains of human subjects with various forms of NCL and the silver-stained gels from their study contain a number of proteins with apparent molecular weights greater than 25 kDa that were not identified (Hall et al 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional proteins are variably associated with the isolated storage bodies, but these have not been well characterized. For example, Hall and colleagues analysed the protein compositions of storage bodies isolated from brains of human subjects with various forms of NCL and the silver-stained gels from their study contain a number of proteins with apparent molecular weights greater than 25 kDa that were not identified (Hall et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of different forms of human NCL that each result from mutations in one of at least eight different genes (PPT1, CLN2, CLN3, CLN5, CLN6, CLN8, CTSD and MFSD8) (Siintola et al 2006(Siintola et al , 2007Steinfeld et al 2006;Wisniewski et al 2001). In the majority of these diseases, the major stored proteins are F 0 subunit c of mitochondrial ATP synthase, a 7.6 kDa hydrophobic protein (Buzy et al 1996;Hall et al 1991;Kominami et al 1992;Tyynela et al 1997b) and/or the 16 kDa V 0 subunit c of vacuolar ATPase (Palmer et al 1997). In other forms of the disease, saposins A and D aredog breeds (Awano et al 2006a, b;Jolly and Palmer 1995;Jolly et al 1992Jolly et al , 1994Katz et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Many biochemical studies have been initiated to determine the characteristic cellular defect underlying these diseases. In summary, CLN2-, characterized by lysosomal accumulation of autofluorescent hydrophobic material, a major component of which is mitochondrial ATP synthase subunit c (Haltia et al, 1973;Koenig et al, 1964;Hall et al, 1991;Palmer et al, 1995). Biochemical and molecular studies demonstrated that accumulation of mitochondrial ATP synthase subunit c is not the result of increased expression of the P1 and P2 nuclear genes that encode the protein, nor does the stored protein have a different encoded sequence from that of normal (Ezaki et al, 1995a;Palmer et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Furthermore, protein sequencing and immunological studies have revealed that subunit c of the mitochondrial ATP synthase is the major component of the storage material in Batten disease. 16,17 Autofluorescent storage material is readily visible in mnd/mnd mice at our earliest postnatal time point, P0, with likely involvement during embryonic development.…”
Section: Storage Materials In Rgcsmentioning
confidence: 87%